Quantitative Assessment of Asbestos Fibers in Abdominal Organs: A Scoping Review - Caraballo-Arias, Yohama; Roccuzzo, Francesco; Graziosi, Francesca; Danilevskaia, Nataliia; Rota, Samantha; Zunarellli, Carlotta; Caffaro, Paola; Boffetta, Paolo; Bonetti, Mattia; Violante, Francesco Saverio (La Medicina del Lavoro, 2023)
Background: Quantification of asbestos fibers has been mainly performed in the lung but rarely in other organs. However, this may be relevant to understanding better translocation pathways and the oncogenic effects of asbestos on the human body. Electron microscopy is the best technology available to assess the type of fiber, dimensions, and distribution of asbestos fibers in different tissues and as a biomarker of cumulative dose. Objectives: This scoping review aims to summarize the findings of the studies in which asbestos fibers have been quantified by electron microscopy, occasionally associated with X-ray microanalysis, in normal and pathological tissue of ten abdominal organs. Methods: A scoping review has been performed by searching articles that quantified asbestos fibers in abdominal organs by electron microscopy (Scanning- SEM or Transmission- TEM). Results: The 12 selected studies included 204 cases, and 325 samples were analyzed. The colon and rectum, kidney, bladder, and abdominal lymph nodes were the organs with at least ten samples available with quantification of asbestos fibers. Asbestos fibers were detected in all the abdominal organs considered: the highest value (152,32 million fibers per gram of dry tissue) was found in the colon and was identified using STEM with EDS. Conclusion: The studies included were heterogeneous in terms of exposure and cases, type of samples, as well as analytical techniques, therefore we cannot confirm a specific pattern of distribution in any organ, based on the low homogeneity of the exposure status. The colon is the organ in which the number of fibers is the highest, probably because of exposure arising from both internal distribution of inhaled fibers and ingestion. Additional studies of the number of asbestos fibers in abdominal organs should be made to achieve better representativity.